QUALITY CHARACTERISTICS OF SMOKED BABY AFRICAN CATFISH (Clarias gariepinus) WITH DIFFERENT SMOKING METHOD - Qalbi Salim; Syahrul Syahrul; Bustari Hasan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT                This study aims to determine the quality characteristics of smoked baby African catfish (Clarias gariepinus) with different smoking methods. This research method was carried out experimentally by making smoked baby African catfish using traditional and liquid smoking methods. The research data were analyzed using the T-test and presented in tables and figures. The results showed that smoked baby African catfish with the traditional and liquid smoking methods were significantly different from proximate and organoleptic value. Smoked baby African catfish with the traditional and liquid smoking method had an average value of ash content was 11.44% and 9.24%, moisture content was 19.64% and 22.34%, protein content was 30.38% and 32.38%, fat content was 13.93% and 16.39%, respectively. Meanwhile smoked baby catfish with the traditional and liquid smoking method had an average of appearance was 6.38 and 7.32, smell 6.86 and 7.45, taste 7.32 and 6.86, texture 6.64 and 6,78. Total plate number analysis or TPC for the 8th day of storage showed that the traditional smoking method contained 4.49x106 colony/gr while the liquid smoking method showed a value of 3.25x106 colony/gr. Keywords: African catfish, traditional smoking method, liquid smoking method